Analysis of the Response and Efforts of The Government of Vietnam in Tackling COVID-19 - Rosy, Afifah Fidina; Melania, Chantika Wuragil Budhi; Yuvanti, Dita Aprilia (Journal of ASEAN Dynamics and Beyond, 2020)
COVID-19 pandemic is considered a big challenge for every country in the world. This pandemic has had a significant impact on both the public health sector and the economic sector. As a country directly contiguous to China, Vietnam is one of the countries affected by the virus's spread. Even so, Vietnam can be categorized as a country recognized as successful in stemming this pandemic's spread. It can be seen from the absence of cases of death caused by COVID-19. Therefore, this paper is written to analyze the government of Vietnam's steps to successfully handle this pandemic and how government conditions can affect the success rate. The results obtained are, the success to tackle the COVID-19 is highly influenced by the background of the political system and governance in Vietnam and the existence of good coordination between government institutions. Moreover, the success factors are also influenced by the efforts taken throughout time to improve public services quality